Análise das condições de saúde de mulheres no puerpério - Silva, Layla Santana Correa da (2022)
Introduction: Qualified physical-based care in prevention is essential for the use of a comfortable and essential care methodology, with the use of a comfortable and essential care methodology, with the use of a safe and familiar care methodology. Objective:. To analyze the conditions of physical, emotional, social and cultural adaptation of postpartum women. Method: It was a study with a qualitative approach With puerperal women in the period from the 30th to the 45th day, who had gone through the experience of normal birth or cesarean section in the city of Campo Grande-MS. Google Meet app. The collection period took place from May to August 2021, and the data were transcribed and stored for further analysis. Bardin Analysis was used to analyze qualitative data, supported by the theoretical framework in Theories of Social RepresentationsResults:Through the data so far results produced articles: through the data. The first is an integrative review, considering the descriptors of quality of life, puerperium and nursing care, literature articles that talk about care practices that contribute to improving the lives of these women. The second was of a qualitative approach describing the tests and the experience of the primordial experience in the pandemic. Final Considerations: This study made it possible to understand the meanings of being a puerperal woman. It is clear that nursing professionals are recognized as individualities, cultural, physiological and adapted to this period to contribute in the best way to the quality of life of these women. Descriptors: Women's Health; Postpartum period; Postpartum Depression; Care Nursing; Quality of Life.